2018
DOI: 10.1111/jopy.12388
|View full text |Cite
|
Sign up to set email alerts
|

The personalities of Danish MPs: Trait‐ and aspect‐level differences

Abstract: The inclusion of the aspect level explains null findings at the Big Five level and adds important nuances to the personality portrait of political elites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 17 publications
5
30
0
Order By: Relevance
“…Thus, for instance, Caprara et al (2003) assessed the personality of 103 Italian politicians and revealed significantly higher levels of extraversion and agreeableness in politicians when compared with the general public; a similar study of women MPs in Italy found that they scored higher than women voters with respect to extraversion, emotional stability and openness (Caprara et al 2010). Joly et al (2018) found that Belgian MPs score particularly high in conscientiousness and emotional stability, and Nørgaard and Klemmensen (2018) found that Danish MPs were more extravert, conscientious and open than the average Danish voter.…”
Section: The Personality Of Populistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for instance, Caprara et al (2003) assessed the personality of 103 Italian politicians and revealed significantly higher levels of extraversion and agreeableness in politicians when compared with the general public; a similar study of women MPs in Italy found that they scored higher than women voters with respect to extraversion, emotional stability and openness (Caprara et al 2010). Joly et al (2018) found that Belgian MPs score particularly high in conscientiousness and emotional stability, and Nørgaard and Klemmensen (2018) found that Danish MPs were more extravert, conscientious and open than the average Danish voter.…”
Section: The Personality Of Populistsmentioning
confidence: 99%
“…In the case of political elites, the lack of direct contact between the researchers and the subjects makes these two approaches unpractical. Some studies were able to collect survey data directly from the elites themselves (Dietrich et al 2012;Joly et al 2018;Nørgaard and Klemmensen 2018), but these studies are isolated and concern very specific populations. A second approach for the study of the personality of political elites consists of relying on psychohistoric analyses of secondary data, such as content analysis of political speeches, for instance via machine learning techniques (Ramey et al 2016(Ramey et al , 2017.…”
Section: Measuring Candidates' Personality Via Expert Ratingsmentioning
confidence: 99%
“…Some studies used self-reported survey measures (Dietrich et al, 2012;Joly et al, 2018;Nørgaard & Klemmensen, 2019;Scott & Medeiros, 2020), but these studies usually concern specific populations (e.g., municipal candidates in two Canadian provinces, Scott & Medeiros, 2020). In the future, initiative such as the Comparative Candidate Survey (CCS) ii might change the situation and provide comparative cross-sectional data about the personality of candidates in multiple contexts, but such data is all but inexistent today.…”
Section: Dark Triad and Electoral Successmentioning
confidence: 99%
“…Candidates in our dataset score particularly high on average in extraversion and conscientiousness, in line with trends found in several other studies. For instance, Caprara et al (2003) show significantly higher levels of extraversion in politicians when compared with the general public, Joly, Soroka, and Loewen (2018) show that Belgian MPs score particularly high in conscientiousness, and Nørgaard and Klemmensen (2018) found that Danish MPs were more extraverted, conscientious (and open) than the average Danish voter. Schumacher and Zettler (2019) report that Danish politicians score higher in honesty-humility than voters, which goes somehow against the trend in our dataset where narcissism is the single higher average score for politicians across the eight personality traits; to be sure, low scores on the HEXACO inventory (which includes the honestyhumility trait) does not necessarily equate with high scores on specific traits within the Dark Triad (Spain, Harms, and LeBreton 2014).…”
Section: Personality Measuresmentioning
confidence: 96%